2006
DOI: 10.1101/gad.1410406
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional regulation of the circadian clock of cyanobacteria and Neurospora

Abstract: Circadian clocks are self-sustained oscillators modulating rhythmic transcription of large numbers of genes. Clock-controlled gene expression manifests in circadian rhythmicity of many physiological and behavioral functions. In eukaryotes, expression of core clock components is organized in a network of interconnected positive and negative feedback loops. This network is thought to constitute the pacemaker that generates circadian rhythmicity. The network of interconnected loops is embedded in a supra-net via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 124 publications
(233 reference statements)
1
76
0
1
Order By: Relevance
“…There are also positive feedback mechanisms involving the influence of frq expression on wc-1 and wc-2 activity and an important role played by post-translational modifications and protein degradation. Details may be found in recent reviews (Lakin-Thomas and Brody 2004;Liu 2005;Brunner and Schafmeier 2006;Dunlap 2006;Liu and Bell-Pedersen 2006).…”
Section: Ircadian Rhythms Are Biological Rhythms Withmentioning
confidence: 99%
“…There are also positive feedback mechanisms involving the influence of frq expression on wc-1 and wc-2 activity and an important role played by post-translational modifications and protein degradation. Details may be found in recent reviews (Lakin-Thomas and Brody 2004;Liu 2005;Brunner and Schafmeier 2006;Dunlap 2006;Liu and Bell-Pedersen 2006).…”
Section: Ircadian Rhythms Are Biological Rhythms Withmentioning
confidence: 99%
“…Such multi-site modifications are widespread in cellular biology with multi-site modifications playing important regulatory roles in many contexts and in many cell types [1,2]. They are believed to play important roles in inflammation pathways and are implicated in important disorders [3][4][5]. The multi-site modification status of a protein has been referred to as a dynamic 'molecular barcode', controlling signal transduction and downstream effects.…”
Section: Introductionmentioning
confidence: 99%
“…More details, in a recent review of the proteins involved in the Neurospora clock function, are found in an up-to-date and clear summary (Dunlap 2006). Other recent articles and reviews provide further information (Brunner and Schafmeier 2006;de Paula et al 2006;Liu and Bell-Pedersen 2006). In addition, a review of the Neurospora rhythm indicates that its inherent complexities are characteristic of a multioscillator system (Lakin-Thomasand Brody 2004).…”
mentioning
confidence: 99%